Superoxide Dismutase of Micrococcus sp. S2 and Its Involve in Paraquat Detoxification - Sebastian Margino; Erni Martani; Medhina Magdalena (Indonesian Journal of Biotechnology, 2007)
As an active ingredient of herbicide, paraquat will induce formation of superoxide radicals. The previousresearch succeeded in isolating paraquat degrading bacteria from peat soil, Micrococcus sp. S2, that tolerant to highconcentration of paraquat. An anti-oxidative enzyme, namely superoxide dismutase (SOD, EC.1.15.1.1), wasbelieved to be responsible for the paraquat tolerance. This research was conducted to study the characteristic of theSOD synthesize by Micrococcus sp. S2 and its ability on neutralize superoxide which arise from paraquat reoxidation.To observe the effect of paraquat on Micrococcus sp. S2, the bacteria was grown in 10% Luria Bertani brothmedium amended with several concentrations of paraquat, from 0 (control) up to 100 mg/ml. Within incubationtime of 72 hours, bacterial growth, activity of superoxide dismutase and paraquat residue were analyzed. Theisozymes of superoxide dismutase were distinguished using two kinds of specific inhibitor, namely HO and KCN. 2 2The results showed that paraquat significantly inhibit the growth of Micrococcus sp. S2. The higher paraquatcocentration in the medium caused the higher growth inhibition. However, the bacteria is still survive in the mediumcontaining toxic herbicide, and this ability was suggested related to superoxide dismutase activity in removing thesuperoxide radicals. Analysis using gel electrophoresis indicated that at least three types of SOD isozyme weresynthesized by Micrococcus sp. S2; they were Ferri-SOD (Fe-SOD), Mangani-SOD (Mn-SOD), and the last one wassuspected to be the Cupro Zinc-SOD (CuZn-SOD). The Mangani-SOD was suspected to play an important roles ondetoxifying superoxide which arise from paraquat oxidation.Keywords : Micrococcus sp.S2, paraquat, superoxide dismutase, isozymes